Therapeutic improvements expected in the near future for schizophrenia and schizoaffective disorder: an appraisal of phase III clinical trials of schizophrenia-targeted therapies as found in US and EU clinical trial registries. (2nd May 2016) - Garay, Ricardo P.; Citrome, Leslie; Samalin, Ludovic; Liu, Chen-Chung; Thomsen, Morten S.; Correll, Christoph U.; Hameg, Ahcène; Llorca, Pierre-Michel
ABSTRACT: Introduction : In this review, the authors describe medications in phase III of clinical development for schizophrenia and schizoaffective disorder, and provide an opinion on how current treatment can be improved in the near future. Areas covered : Recent (post 2013) phase III clinical trials of schizophrenia-targeted therapies were found in US and EU clinical trial registries. Two hundred fifty-three trials were identified, that included 16 investigational compounds. The antipsychotics brexpiprazole and cariprazine have been approved in the US, and although both are dopamine D2 receptor partial agonists, they differ markedly in their pharmacodynamic profiles. Encenicline and valbenazine are first-in-class candidates for treatment of cognitive impairment associated with schizophrenia (CIAS) and tardive dyskinesia, respectively. Eleven add-on compounds were previously approved for other therapeutic indications and are for the most part being studied at academic medical centers and smaller pharmaceutical companies for negative symptoms and CIAS or for specific populations (comorbidities, antipsychotic-induced obesity). Expert opinion : Promising new agents are emerging for schizophrenia and schizoaffective disorder. In addition to better-tolerated antipsychotics that treat positive symptoms, we could see the arrival of the first effective drug for negative symptoms and CIAS, which would strongly facilitate the ultimate goal of recovery in persons with schizophrenia.